Genomic Evolution of the SARS-CoV-2 Omicron Variant in Córdoba, Argentina (2021–2022): Analysis of Uncommon and Prevalent Spike Mutations - Nadia B. Olivero; Victoria E. Zappia; Pablo Gargantini; Candela Human-Gonzalez; Luciana Raya-Plasencia; Judith Marquez; Lucia Ortiz-Batsche; Mirelys Hernandez-Morfa; Paulo R. Cortes; Danilo Ceschin; Mariana Nuñez-Fernandez; Daniel R. Perez; et al. (Viruses)
Understanding the evolutionary patterns and geographic spread of SARS-CoV-2 variants, particularly Omicron, is essential for effective public health responses. This study focused on the genomic analysis of the Omicron variant in Cordoba, Argentina from 2021 to 2022. Phylogenetic analysis revealed the dominant presence of BA.1 and BA.2 lineages, with BA.5 emerging earlier than BA.4, aligning with observations from other regions. Haplotype network analysis showed significant genetic divergence within Omicron samples, forming distinct clusters. In comparison to global datasets, we identified mutations in the Omicron genomes (A27S, Y145D, and L212I) situated within the NTD region of the Spike protein. These mutations, while not widespread globally, showed higher prevalence in our region. Of particular interest were the Y145D and L212I substitutions, previously unreported in Argentina. In silico analysis revealed that both mutations impact the binding affinity of T-cell epitopes to HLA type I and II alleles. Notably, these alleles are among the most common in the Argentinian population, with some associated with protection against and others with susceptibility to SARS-CoV-2 infection. These findings strongly suggest that these prevalent mutations likely influence the immunogenicity of the Spike protein and contribute to immune evasion mechanisms. This study provides valuable insights into the genomic dynamics of the Omicron variant in Cordoba, Argentina and highlights unique mutations with potential implications for COVID-19 vaccines.